At what step did the error started?
(x+1)2=x2+2x+1
Step 1: (x+1)2−(2x+1)=x2
Step 2: (x+1)2−(2x+1)−x(2x+1)=x2−x(2x+1)
Step 3: (x+1)2−(x+1)(2x+1)+41(2x+1)2=x2−x(2x+1)+41(2x+1)2
Step 4: [(x+1)−21(2x+1)]2=[x−21(2x+1)]2
Step 5: (x+1)−21(2x+1)=x−21(2x+1)
Step 6: x+1=x
Therefore, 1=0
#Algebra
#AlgebraicIdentities
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Step 5 corrected to: (x + 1) - (1/ 2) (2 x + 1) = (1/ 2) (2 x + 1) - x would be all right.
At step5